Efficacy and safety of IL-17 inhibitors for the treatment of ankylosing spondylitis: a systematic review and meta-analysis - Yin, Yufeng; Wang, Mingjun; Liu, Mengru; Zhou, Erye; Ren, Tian; Chang, Xin; He, Michun; Zeng, Keqin; Guo, Yufan; Wu, Jian (Arthritis research & therapy, 2020)
To systematically assess the efficacy and safety of IL-17 inhibitors in patients with active ankylosing spondylitis. A systematic review of the literature was performed for randomized controlled trials (RCTs) concerning IL-17 inhibitors in patients with ankylosing spondylitis. Meta-analyses were used to determine the efficacy and safety of the IL-17 inhibitors in the treatment of these patients. The primary endpoint was predefined as the proportion of patients with at least 20% improvement in the Assessment of Spondyloarthritis International Society (ASAS20) response criteria at week 16, and the secondary endpoint was defined as ASAS40 at week 16. Six phase III randomized, double-blind, placebo-controlled trials including 1733 patients (1153 patients received IL-17 inhibitors, including secukinumab or ixekizumab, whereas 580 patients received a placebo as comparators) were included. At week 16, the IL-17 inhibitor regimen produced a significant increase in the ASAS20 response rate (RR = 1.63, 95% CI 1.45 to 1.84, p = 0.00) and the secondary endpoint ASAS40 response rate (RR = 2.12, 95% CI 1.75 to 2.56, p = 0.00) versus those for the placebo. With respect to the safety profile, more treatment-emergent adverse events (RR = 1.11, 95% CI 1.01 to 1.22, p = 0.03) and non-severe infections (RR = 1.82, 95% CI 1.40 to 2.37, p < 0.001) were described after treatment with IL-17 inhibitors than after treatment with placebo, while no increased risk of other adverse events was indicated after IL-17 inhibitor therapy, including death, discontinuation due to adverse events, or serious adverse events. IL-17 inhibitors produced favorable response rates but an increased risk of non-severe infections in the treatment of active ankylosing spondylitis.